2018
DOI: 10.1016/j.jcf.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Age-related heterogeneity in dental caries and associated risk factors in individuals with cystic fibrosis ages 6–20 years: A pilot study

Abstract: Younger children with CF may be protected from caries, but there is apparent loss of protection in early adolescence associated with multiple risk factors. Additional studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
4
19
4
Order By: Relevance
“…This is the same questionnaire that was used for a previously published study. 18 Caregivers completed the questionnaire with input solicited from the child as needed. Children received a dental screening.…”
Section: Study Proceduresmentioning
confidence: 99%
“…This is the same questionnaire that was used for a previously published study. 18 Caregivers completed the questionnaire with input solicited from the child as needed. Children received a dental screening.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Oral health is an important component of overall health in the general population, but there are few studies in CF. A prospective, observational study in 85 people with CF, ages 6 to 20 years, found that when compared with control, children with CF aged 6 to 9 years had a lower rate of caries than controls, but there were no differences in the group aged 10 to 20 years . A number of risk factors were found to explain the loss of protection against carries as a patient with CF age.…”
Section: Multisystem Effects Of Cystic Fibrosismentioning
confidence: 99%
“…A prospective, observational study in 85 people with CF, ages 6 to 20 years, found that when compared with control, children with CF aged 6 to 9 years had a lower rate of caries than controls, but there were no differences in the group aged 10 to 20 years. 41 A number of risk factors were found to explain the loss of protection against carries as a patient with CF age. Similar findings were discussed in a systematic review of dental health in CF, with CF patients having equal or lesser caries risk and more enamel defects in permanent dentition than non-CF controls.…”
Section: Oral Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The association between CF and caries risk has been established in young children, but relatively less information exists on its association with periodontal inflammation. [3][4][5][6] Although children with CF are reported to have a higher prevalence of calculus due to deregulated calcium and phosphate levels in their saliva, 3 it is not conclusive if other salivary factors are associated with and/or reflect CF. There is an increasing evidence that expression of triggering receptor expressed on myeloid cells 1 (TREM-1), along with its putative ligand peptidoglycan recognition protein 1 (PGLYRP1), is significantly increased in saliva in the presence of chronic inflammatory diseases including periodontal disease.…”
Section: Introductionmentioning
confidence: 99%